“Estimación de captura de carbono en cuatro especies de pasturas y uno de maíz como testigo en cuñumbuque-San Martín” - Chávez Bazán, Fredy (2003)
The present work takes as title Estimate of capture of Carbon in four species of grasses: Brachiaria brizantha, Brachiaria decumbes, Pennisetum purpureun and Saccharum sinensis in Cuñumbuque - San Martin", the objectives were to Quantify the reservations of Carbon of the air biomass, in the trash and in the floor in four species of grasses: Brachiaria brizantha, Brachiaria decumbes, Pennisetum purpureun and Saccharum sinensis, in the District of Cuñumbuque, County of you Lick, Department of San Martin and to Establish the pertinent physiologic relationships among the treatments evaluated in relation to a witness (corn) in the District of Cuñumbuque, County of you Lick, Department of San Martin. Likewise the Design of Blocks was used Totally at random with 5 treatments and 4 repetitionf;. T~e treatments were: T ~ Saccharum sinensis, T 2 Brachiaria decumbes, T 3 Brachiaria brizantha, T4 Pennisetum purpureun and Ts Zea mays. The results hurtled that the biggest accumulation of carbon in the air biomass you obtain with Pennisetum \ purpureun wiíh a total of 11 865.30 Kg/ha. The biggest accumulation of carbon in the trash of the floor was obtained with Brachiaria decumbes with a total of 16 469.00 Kg/ha. likewise Brachian"a decumbes was the gramineous one that presentad the biggest accumulation of carbon in the properly this floor, with a total of 19 890.00 Kg/ha. ANO lastly the biggest accumulation of total carbon was presented in Brachiaria decumbes with a total accumulated in floor, trash and air biomass of 38 774.00 Kg/ha. The cultivation of Corn (witness) the treatment that she obtained the smallest quantity in accumulated carbon was (1 am accustomed to, trash and air biomass), with an accumulated totai of 4 901.30 Kg/ha.